State/nation/transnation : perspectives on transnationalism in the Asia-Pacific - Yeoh, Brenda S. A.; Willis, Katie, 1968- (Transnationalism. Routledge research in transnationalism ;, 2004)
Setting the book within a theoretical framework, the authors explore a range of themes such as migration, identity and citizenship in chapters on China, the Philippines, Malaysia, Vietnam, Japan, Indonesia, Australia, Singapore and Cambodia.